Evidance Based Intervensi Psikologi Terhadap peningkatan strategi DOTS Pada Pasien Tuberkulosis: A Systematic Review - Gevi Melliya Sari; Bernadetta Germia Aridamayanti; Sariati Sariati; Dwi Uswatun Sholikhah; Cahya Mustika Narendri; Wimar Anugrah Romadhon (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Psychological problems are one of the factors that influence tuberculosis patient compliance. Psychological intervention is needed to help patients cope with stressors experienced during the treatment period of at least 6 months and increase patient compliance in undergoing treatment. Objective: To outline some of the benefits of psychological interventions that can help pulmonary tuberculosis patients follow treatment. Method: The database used in this study is Scopus, Google Scholar, and Pubmed is limited to the last 5 years of publication from 2016 to 2020, full-text article in English. The keywords used are "Psychological Intervention", "OR", "AND", "Emotional Intervention",”AND”, "Tuberculosis". This systematic review uses 9 articles that fit the inclusion criteria. Results: Psychological interventions can be applied independently or comprehensively provided with peer support, home visits, counseling, and health education. The benefits of psychological interventions can reduce depression, anxiety, stress, increase self-efficacy, improve self-reliance, increase patient knowledge, increase social support and improve patient compliance in treatment. Conclusion: Psychological intervention has many benefits in helping patients undergo a period of Tuberculosis treatment. Suggestion: Psychological intervention can be applied in health care both during patient control and home visit activities and telenursing via telephone. Keywords: emotional intervention; psychological intervention; Tuberculosis ABSTRAK Latar belakang: Masalah psikologi menjadi salah satu faktor yang mempengaruhi kepatuhan pasien Tuberkulosis. Intervensi psikologi sangat dibutuhkan untuk membantu pasien mengatasi stressor yang dialami selama masa pengobatan minimal 6 bulan serta meningkatkan kepatuhan pasien dalam menjalani masa pengobatan. Tujuan: Untuk menguraikan beberapa manfaat intervensi psikologi yang dapat membantu pasien Tuberkulosis paru dalam menjalani pengobatan Metode: Database yang digunakan dalam penelitian ini adalah Scopus, Google Schoolar dan Pubmed terbatas untuk publikasi 5 tahun terakhir dari 2016 hingga 2020, full text article dengan berbahasa Inggris. Kata kunci yang digunakan adalah “Psychological Intervention” ,”OR”, “AND”, “ Emotional Intervention”, “AND”, “Tuberculosis”. Systematic review ini menggunakan 9 artikel yang sesuai dengan kriteria inklusi. Hasil: Intervensi psikologi dapat diterapkan secara mandiri maupun diberikan secara komprehensif dengan dukungan kelompok sebaya, home visit, konseling dan pendidikan kesehatan. Manfaat intervensi psikologi yaitu dapat menurunkan depresi, kecemasan, stress, meningkatkan self efficacy, meningkatkan self reliance, meningkatkan pengetahun pasien, meningkatkan dukungan sosial dan meningkatkan kepatuhan pasien dalam menjalani pengobatan. Simpulan: Intervensi psikologi memiliki banyak manfaat dalam membantu pasien menjalani masa pengobatan Tuberkulosis. Saran: Intervensi psikologi dapat diterapkan dalam pelayanan kesehatan baik pada saat pasien kontrol maupun kegiatan kunjungan rumah dan melalui telenursing via telephone. Kata kunci: emotional intervention; psychological intervention; Tuberculosis